Mapping collaboration in open source geospatial ecosystem - Shao, Jianhua; Kuk, George; Anand, Suchith; Morley, Jeremy; Jackson, Mike; Mitchell, Tyler (Wiley, 2012)
Over the last decade, there has been a tremendous growth and exploitation of open source geospatial software and technologies. A combination of factors is driving this momentum, including the contributions made by hundreds of developers and the leading role played by the Open Source Geospatial Foundation (OSGeo), aiming primarily to support and promote the collaborative development of open source geospatial technologies and data. This article seeks to map out the social history of collaborative activities within the OSGeo ecosystem. We used the archival logs of developers' contributions, specifically looking for boundary spanning activities where contributions crossed multiple projects. The analysis and visualization of these activities allow us to have a better understanding of the role of boundary spanning in the resourcing of each project, the incubation mechanism advocated by OSGeo, and the significance of the social interrelatedness among projects. The data consisted of the subversion (SVN) commit history made by individual developers in the programming code repository. We applied several network analytical and visualization techniques to explore the data. Our findings indicate that more than one in seven developers spanned multiple projects which potentially had the effects of shaping the projects' directions, and increased knowledge flow and innovation. In addition, the OSGeo's incubation mechanism provided an important encouragement for boundary spanning and increased knowledge sharing. By studying the social history of contributions, further tools can be developed in future to assist tracking of the social history, and make developers mindful of the significance of the interdependence among projects and hence continuously contribute to the health of the OSGeo ecosystem.